新加坡模式对中国现代化道路选择的启迪与借鉴 = The policy implications of the Singapore model for China's economic development - 吴乐进 Wu, Lejin (2008)
This thesis analyses the process of Singapore's development and studies the implications for China's efforts at modernization, with particular emphasis on the economic factor, the political factor, and the social factor.